(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this research is the optimal portfolio selection using the Fuzzy Analytic Hierarchy Process (FAHP). This research is applied in terms of objective and descriptive-analytical in terms of data collection and processing. The assessment models of strategic programs such as the FAHP are utilized to conduct this research. The studied population consists of all companies listed on Tehran Stock Exchange during 2014-2019 and 7 companies are considered as the samples. The descriptive statistics including the demographic data of statistical sample such as the tables of frequency distribution, descriptive diagram, etc, are utilized for data analysis in this research and also the inferential statistics by FAHP is used for weighting the options. According to the results, the prioritization of portfolio selection criteria is as follows: Expected return, liquidity and risk criterion. Furthermore, the prioritization of studied listed companies is as follows: Esfahan’s Mobarakeh Steel Company, Pipe and Machine Manufacturing Company of Iran, Borujerd textile Company, Rolling Mill & Steel Production Co., IRAN Merinos Co, Sadid Industrial Group, and Tous Wool Weaving Co.